Pembelajaran Berkualitas Berbasis Deep Learning Dan Penguatan Karakter Dalam Meningkatkan Kompetensi Guru Pendidikan Dasar - Subowo Dikdayana (Yayasan Al-Afif, 2026)
Primary education plays a strategic role in shaping students’ knowledge, attitudes, and character; therefore, learning quality and teacher competence are key determinants of sustainable educational quality. However, learning practices in primary schools are still dominated by surface learning approaches focused on memorization and short-term cognitive outcomes, which limit deep understanding and character development. This study aims to conceptually examine the relationship between deep learning–based quality learning, character strengthening, and the enhancement of primary school teacher competence. The study employs a qualitative approach using a literature review method through critical analysis and theoretical synthesis of reference books, scholarly journal articles, and relevant educational policy documents. The findings indicate that deep learning–based instruction promotes conceptual understanding, higher-order thinking skills, and character internalization when supported by teachers’ pedagogical, professional, personal, and social competencies. In conclusion, the integration of deep learning, character education, and teacher competence forms an interconnected conceptual framework for achieving quality learning in primary education, contributing to a holistic perspective on meaningful learning development.